EFEKTIVITAS MEDIA PEMBELAJARAN PANCAMAN (PAPAN TANCAP TEPAT KEBERAGAMAN) DALAM MENINGKATKAN LITERASI KEBUDAYAAN PESERTA DIDIK KELAS II PADA MATA PELAJARAN PKN DI SD SUKOMULYO NGAGLIK - Okta Reza, Nia; Noor Muhammad, Azamul Fadhly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of cultural and civic literacy among fourth- grade students at SD Negeri sukomulyo. This condition was reflected in students’ limited understanding of Indonesia’s socio-cultural diversity, low interest in learning Pancasila Education, and the lack of innovative learning media used in the classroom. To address these issues, the researcher implemented Pancaman (Papan Tancap Tepat Keberagaman/Diversity Pin Board), an interactive visual learning medium designed to help students understand various aspects of Indonesian cultural diversity in a concrete and engaging manner. The objective of this study was to determine the effectiveness of Pancaman learning media in improving students’ cultural and civic literacy. This research employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The population consisted of 35 fourth-grade students at SD, while the sample comprised 16 students selected through a cluster sampling technique. Data were collected through tests, observations, and documentation. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing with the assistance of SPSS version 18. The findings revealed that the use of Pancaman learning media had a significant positive effect on students’ cultural and civic literacy. The average post-test score reached 84.38, which was higher than the pre- test score. Furthermore, the hypothesis testing results showed a significance value (Sig. 2-tailed) of 0.0022, which was lower than 0.05 (0.0022 < 0.05). Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. These results indicate that PANCAMAN learning media is effective in improving the cultural and civic literacy of fourth-grade students in Pancasila Education at SD Negeri Sukomulyo.